Fatigue Characterization on a Cast Aluminum Beam of a High-Speed Train Through Numerical Simulation and Experiments - Weiyuan Dou (SpringerOpen, 2021)
Abstract The cast aluminum beam is a key structure for carrying the body-hung traction motor of a high-speed train; its fatigue property is fundamental for predicting the residual life and service mileage of the structure. To characterize the structural fatigue property, a finite element-based method is developed to compute the stress concentration factor, which is used to obtain the structural fatigue strength reduction factors. A full-scale fatigue test on the cast aluminum beam is designed and implemented for up to ten million cycles, and the corresponding finite element model of the beam is validated using the measured data of the gauges. The results show that the maximum stress concentration occurs at the fillet of the supporting seat, where the structural fatigue strength reduction factor is 2.45 and the calculated fatigue limit is 35.4 MPa. Moreover, no surface cracks are detected using the liquid penetrant test. Both the experimental and simulation results indicate that the cast aluminum beam can satisfy the service life requirements under the designed loading conditions.